2020
DOI: 10.1101/2020.12.04.411553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of sigma-1 receptor in organization of endoplasmic reticulum signaling microdomains

Abstract: SUMMARYSigma 1 receptor (S1R) is a 223 amino acid-long transmembrane endoplasmic reticulum (ER) protein. S1R modulates activity of multiple effector proteins but its signaling functions are poorly understood. We here test the hypothesis that biological activity of S1R in cells can be explained by its ability to interact with cholesterol and to form cholesterol-enriched microdomains in the ER. Using reduced reconstitution systems, we demonstrate direct effects of cholesterol on S1R clustering. We identify a nov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 99 publications
6
16
0
Order By: Relevance
“…S1R activation releases the inhibitory interaction with BiP and allows for the S1R to interact with various partners inside and outside of the MAMs, including the inositol-1,4,5-triphosphate receptor type 3 (InsP 3 R3) [34,42]. Our recent results [59] and previous studies [57] suggest that a direct, high-affinity association of the S1R with cholesterol and ceramides may also contribute to S1R targeting by MAMs.…”
Section: Intracellular Localization Of the S1rmentioning
confidence: 63%
See 4 more Smart Citations
“…S1R activation releases the inhibitory interaction with BiP and allows for the S1R to interact with various partners inside and outside of the MAMs, including the inositol-1,4,5-triphosphate receptor type 3 (InsP 3 R3) [34,42]. Our recent results [59] and previous studies [57] suggest that a direct, high-affinity association of the S1R with cholesterol and ceramides may also contribute to S1R targeting by MAMs.…”
Section: Intracellular Localization Of the S1rmentioning
confidence: 63%
“…Recently, we demonstrated that cholesterol promotes the formation of S1R domains in a model lipid bilayer system [59]. Using GUVs with reconstituted fluorescent-labeled S1R, we observed that cholesterol was sufficient to cause clustering of recombinant S1R in the absence of any other proteins [59].…”
Section: Interaction Of S1r With Er Membranesmentioning
confidence: 96%
See 3 more Smart Citations